24.58% efficient commercial n‐type silicon solar cells with hydrogenation. (12th September 2021) - Chen, Ran; Wright, Matthew; Chen, Daniel; Yang, Jie; Zheng, Peiting; Zhang, Xinyu; Wenham, Stuart; Ciesla, Alison
Abstract: Tunnelling oxide passivated contact (TOPCon) solar cells are gaining significant commercial interest, due to the potential for high efficiency. Industrially, this passivated contact scheme is typically coupled with an n‐type Czochralski (Cz) wafer. JinkoSolar Holding Co., Ltd. is one of the leading manufacturers that are producing n‐type TOPCon solar cells (referred to as 'HOT' cells) on a commercial scale. In this work, the influence of a post‐cell hydrogenation step, using illumination from an LED light source, on the performance and stability of n‐type TOPCon solar cells is investigated. The incorporation of this additional hydrogenation treatment led to an average efficiency enhancement of 0.64%abs on a batch of 50 cells made in an industrial environment. This significant improvement was caused by a 6.9 mV and 1.04%abs increase in open‐circuit voltage ( V OC ) and fill factor (FF), respectively. We also assessed the stability and found almost no light‐ and elevated temperature‐induced degradation (LeTID) in hydrogenated n‐type TOPCon cells. Testing at 70 ± 5°C under 1‐sun illumination revealed that the maximum degradation is limited to 0.06%rel . Following further stability testing, the efficiency increased beyond the initial value, up to 0.4%rel increase after 120 h. By incorporating this hydrogenation process into the production, an average line efficiency of 24.08% and V OC of 707.5 mV was achieved. The champion cell from the batch displayed an efficiency of 24.58%, as certified by measurement at the Chinese Academy of Sciences. Abstract : Hydrogenation processes applied to Jinko Solar's n‐type TOPCon "HOT" cells provide 0.64%abs efficiency improvements. Stability testing shows 0.06%rel maximum degradation before recovering to 0.4%rel above the starting efficiency within 126 h. On lifetime precursors, hydrogenation processes improve the average i V OC from 720.7 to 727.9 mV. A batch of HOT cells incorporating hydrogenation from Jinko's R&D line achieved a champion cell with 24.58% efficiency and 718.5‐mV V OC and an average line efficiency of 24.08% and 707.5‐mV V OC .